The IASP classification of chronic pain for ICD-11 - chronic secondary headache or orofacial pain - Benoliel, Rafael; Svensson, Peter; Evers, Stefan; Wang, Shuu-Jiun; Barke, Antonia; Korwisi, Beatrice; Rief, Winfried; Treede, Rolf-Detlef (Pain, 2019)
AbstractThis article describes chronic secondary headache and chronic orofacial pain (OFP) disorders with respect to the new International Classification of Diseases (ICD-11). The section refers extensively to the International Classification of Headache Disorders (ICHD-3) of the International Heada
Gesehen am 25.06.2019